Anxiety and depression in pregnant women (Research, Society and Development, 2022)
In the gestational phase, the woman's body undergoes several changes, so the pregnant woman is susceptible to triggering a certain type of mental disorder throughout pregnancy, including depression. Several social factors may be linked to depression, such as: psychological and biological elements, these aspects predispose to develop diseases in prenatal care. Anxiety is classified as one of the risk factors for pregnancy, and can then harm the fetus, bringing negative results such as prematurity, low weight, fit index and deficit in fetal evolution. Its physical and psychological development is compromised, resulting in obstetric problems such as abortion and postpartum depression. The objective of this study was to know the occurrence of anxiety and depression among pregnant women. This is an integrative review of the literature, the method used consists of evidence-based practice, whose main objective is to gather relevant information focused on a given theme, to achieve synthesized and compare other studies in a more complete and organized way. Symptoms of depression and anxiety have often affected women during their gestational period. Depression carries with it a great emotional weight that implies in your physical and mental health being a risk factor for PPD. It was concluded that the data obtained indicated that anxiety and depression in women may vary in degrees from mild to intense and pregnant women who have risky pregnancies indicated higher rates.